Cost efficiency of Yemen Islamic banks: An inefficiency effects approach (2002-2014) - O.A. Bushara, Mohamed; A.M .Aziz, Yaaqob; I. M. Hussain, Abu-Bakr (Gezira Journal of Agricultural Science; Vol 16 No 2 (2018), 2018)
REFERENCES   Battese, G. E. and T. J. Coelli. 1988. Prediction of firm-level technical efficiencies with a generalized frontier production function and panel data. Journal of Econometrics 38(3):387-399. Battese, G. E. and T. J. Coelli. 1992. Frontier production functions, technical efficiency and panel data: with application to paddy farmers in India. Journal of Productivity Analysis 3(1-2):153-169. Battese, G. E. and T. J. Coelli. 1995. A model for technical inefficiency effects in a stochastic frontier production function for panel data. Empirical Economics 20(2):325-332. Bushara, M. and M. Abuagla. 2016. Measuring production efficiency of sorghum small farmers in Rahad Agricultural Scheme season (2011-2012). Journal of Socialomics 5(192):1-10. Bushara, M. O. and M. G. Mohayidin. 2008. Cost efficiency of Malaysian oil and fat industry: An empirical evidence. Sudan Journal of  Agricultural Research 9:135-147. Hasan, M. and J. Dridi. 2011. The effects of the global crisis on Islamic and conventional banks: A comparative study. Journal of International Commerce, Economics and Policy 2(2):163-200. Huang, C. J. and J.-T. Liu. 1994. Estimation of a non-neutral stochastic frontier production function. Journal of Productivity Analysis 5(2):171-180. Isik, I. and M. K. Hassan. 2003. Financial deregulation and total factor productivity change: An empirical study of Turkish commercial banks. Journal of Banking and Finance 27(8):1455-1485. Kumbhakar, S. C., S. A. Ghosh and J. T. McGuckin. 1991. A generalized production frontier approach for estimating determinants of inefficiency in US dairy farms. Journal of Business and Economic Statistics 9(3):279-286. Kyj, L. and I. Isik. 2008. Bank x-efficiency in Ukraine: An analysis of service characteristics and ownership. Journal of Economics and Business 60(4):369-393. McKinnon, R. 1997. Money and capital in economic development. The Brookings Washington DC. Pasiouras, F. 2008. Estimating the technical and scale efficiency of Greek commercial banks: The impact of credit risk, off-balance sheet activities, and international operations. Research in International Business and Finance 22(3):301-318. Pitt, M. M., and L.F. Lee. 1981. The measurement and sources of technical inefficiency in the Indonesian weaving industry. Journal of Development Economics 9(1):43-64. Reifschneider, D. and R. Stevenson. 1991. Systematic departures from the frontier: A framework for the analysis of firm inefficiency. International Economic Review32(3):715-723. Samad, A. and M. K. Hassan. 1999. The performance of Malaysian Islamic bank during 1984-1997: An exploratory study. International Journal of Islamic Financial Services 1(3):1-14. Schmidt, P. and C. K. Lovell. 1979. Estimating technical and allocative inefficiency relative to stochastic production and cost frontiers. Journal of Econometrics 9(3):343-366. Sealey, C. W. and J. T. Lindley. 1977. Inputs, outputs and a theory of production and cost at depository financial institutions. The Journal of Finance 32(4):1251-1266. Sufian, F. and M. Akbar Noor Mohamad Noor. 2009. The determinants of Islamic banks' efficiency changes: Empirical evidence from the MENA and Asian banking sectors. International Journal of Islamic and Middle Eastern Finance and Management 2(2):120-138. Sufian, F. and M. S. Habibullah. 2010. Assessing the impact of financial crisis on bank performance: Empirical evidence from Indonesia. ASEAN Economic Bulletin27(3):245-262. Tecles, P. L. and B. M. Tabak. 2010. Determinants of bank efficiency: The case of Brazil. European Journal of Operational Research 207(3):1587-1598. Weill, L. 2004. Measuring cost efficiency in European banking: A comparison of frontier techniques. Journal of Productivity Analysis 21(2):133-152. Willison, B. 2009. Technology trends in Islamic investment banking. Islamic Finance News 6(19):22-23.